Antibacterial activity of gallic acid and methyl gallate against emerging non-fermenting bacilli - Flores-Maldonado, Orlando; Dávila-Aviña, Jorge; González, Gloria M; Becerril-García, Miguel A; Ríos-López, Ana L (Folia microbiologica, 2025)
Stenotrophomonas maltophilia, Achromobacter xylosoxidans, and Burkholderia cenocepacia are considered emerging pathogens classified as a public health problem due to extensive antimicrobial resistance. Therefore, the discovery of new therapeutic strategies has become crucial. This study aimed to evaluate the antimicrobial activity of gallic acid and methyl gallate against non-fermenting bacteria. The study included five clinical isolates of Stenotrophomonas maltophilia, Achromobacter xylosoxidans, and Burkholderia cenocepacia. The minimum inhibitory concentrations of gallic acid and methyl gallate were determined by the broth microdilution method. Growth curves, metabolic activity, and biofilm formation of each bacterial strain in the presence or absence of phenolic compounds were performed. Finally, the therapeutic efficacy of the compounds was evaluated using an in vivo model. Gallic acid and methyl gallate showed antibacterial activity against bacterial strains in a concentration range of 64 to 256 µg/mL, both compounds reduced bacterial growth and metabolic activity of the strains, even at subinhibitory concentrations. Only, methyl gallate exhibited activity to inhibit the formation of bacterial biofilms. Moreover, gallic acid and methyl gallate increased larval survival by up to 60% compared to 30% survival of untreated larvae in a bacterial infection model in Galleria mellonella. Our results highlight the potential of gallic acid and methyl gallate as therapeutic alternatives for infections by emerging non-fermentative bacteria.
Keywords: Gram-Negative Bacterial Infections; můry; antibakteriální látky; Microbial Sensitivity Tests; Antimicrobial activity; Gallic Acid; kyselina gallová; larva; Animals; lidé; Anti-Bacterial Agents; Biofilms; Humans; zvířata; mikrobiální testy citlivosti; gramnegativní bakteriální infekce; Phenolic compounds; biofilmy; Larva; Burkholderia cenocepacia; Moths; Stenotrophomonas maltophilia; Achromobacter xylosoxidans